Heaney à l’écoute de l’Est : Nouveaux horizons critiques - Franck Miroux (Revue LISA)
This article attempts to assess the impact of Eastern European poetry on Seamus Heaney’s works of criticism. It focuses on two key aspects of Seamus Heaney’s critical thought which are directly connected to the close relationship he developed with Eastern European poetry: the tension between the self and the community and the demands placed on the poet by a group or an institutional body, and the importance of language in discussing poetry, both from an acoustic and from a metaphorical point of view. Finally, the paper tries to determine to what extent such encounters enable the poet to put his own culture into perspective and to broaden his critical horizon.